ENGAGING NON-STATE ACTOR IN SECOND-TRACK DIPLOMACY: A STUDY OF NAHDLATUL ULAMA IN PROMOTING MODERATE ISLAM - Ridwan, Ridwan; Farikhah , Kamilatul; Yanuri, Yusuf R (Balai Penelitian dan Pengembangan Agama Makassar, 2025)
Indonesia employs second-track diplomacy by engaging Islamic mass organizations as non-state actors and undertakes various forms of interfaith diplomacy to promote moderate Islam and achieve global peace. This article explains Nahdlatul Ulama (NU) 's efforts in promoting moderate Islam and addressing several global issues. The authors argue that Indonesia's collaboration with NU in the second-track diplomacy to project itself as a moderate Muslim country and utilize NU's influence to promote peace, tolerance, and interfaith dialogue globally. Hence, this partnership aims to enhance Indonesia's international reputation and address global challenges caused by religious and cultural misunderstandings. Overall, this article enriches the literature on Indonesia's global identity as a moderate Muslim nation shaped by the cooperation between the state and non-state actors.